A New Way of “Thinking” Consciousness: Nietzsche, Wittgenstein, and Neo-Materialism - Aloisia Moser (Religions)
This paper re-examines consciousness through Nietzsche, Wittgenstein, and contemporary neo-materialism, arguing that traditional views overstate its importance and that retreating to the subconscious is inadequate. Using a moth infestation metaphor, it highlights the interconnectedness of sentient and non-sentient beings and advocates for recognizing our shared existence. Nietzsche’s perspectivism shows that human will arises from interdependent life forces, while Wittgenstein’s “form of life” illustrates that meaning comes from shared practices. In one reading of the form of life, religion can be seen as different forms of life. This paper concludes that theology must rethink its focus on human consciousness post the “anthropological turn”, avoiding dualistic body–soul separations. By embracing a holistic view of interconnectedness, we can enrich our understanding of human existence and foster compassionate engagement with diverse life forms, promoting a more integrated and empathetic approach to living.